Analysis of Factors Influencing The Adoption Intention of JakPantau Utilization in Jakarta - Kharisma Putra, Genta Reznanda; Cempaka Mulia, Imas (Jurnal Ilmiah Administrasi Publik, 2026)
This study aims to analyze the factors that influence public adoption intention in utilizing the JakPantau application as a flood disaster mitigation tool in Jakarta. JakPantau is a feature within the Jakarta Kini (JAKI) application that provides real-time information on flood conditions through an automated sensor system integrated with official government data. The research uses a quantitative approach with a mixed-method data collection technique, combining quantitative methods (survey) and qualitative methods (in-depth interviews). The findings indicate that, based on the analysis using the theory of Chuah et al. (2024), the most influential factors on public adoption intention of JakPantau are risk information seeking and social media competence. Meanwhile, the least influential factor is trust in government information. This study provides recommendations to improve the quality of information delivered through JakPantau and to enhance public trust in the data presented, as well as to broaden the reach and frequency of application usage within the community.